Accounting for nonlinearity, asymmetry, heterogeneity, and cross-sectional dependence in energy modeling: US state-level panel analysis - Brantley Liddle (Economies, 2017)
This paper provides an example of several modeling and econometric advances used in the panel estimation of energy demand elasticities. The paper models the demand of total, industrial, and transport energy consumption and residential and commercial electricity consumption by analyzing US state-based panel data. The paper employs recently developed dynamic panel methods that address heterogeneity, nonstationarity, and cross-sectional dependence. In addition, the paper (i) considers possible nonlinear relationships between energy consumption and income without employing polynomial transformations of integrated income; and (ii) allows for and calculates possible asymmetric relationships between energy consumption and price. Finally, the paper models energy efficiency improvements by a nonlinear time trend. To our knowledge no other paper has combined all of the econometric and modeling advances that are applied here. Most of the results conformed to expectations; however, limited to no evidence of nonlinearities and asymmetries were uncovered.
Keywords: C23; Q41; 330; disaggregated energy demand; dynamic common factor panel models; nonstationary; heterogeneous panels; nonlinear; asymmetric relationships; US states